An Evaluation of Regulatory Regimes of Medical Cannabis: What Lessons Can Be Learned for the UK? - Anne Katrin Schlag (Medical Cannabis and Cannabinoids)
This paper evaluates current regulatory regimes of medical cannabis using peer-reviewed and grey literature as well as personal communications. Despite the legalization of medical cannabis in the UK in November 2018, patients still lack access to the medicine, with fewer than 10 NHS prescriptions having been written to date. We look at six countries that have been at the forefront of prescribing medical cannabis, including case studies of the three largest medical cannabis markets in the EU: Germany, Italy, and the Netherlands. Canada, Israel and Australia add global examples. These countries have a more successful history of prescribing medical cannabis than the UK. Their legislations are outlined and numbers of medical cannabis prescriptions are provided to give an indication of how successful their regulatory regime has been in providing patient access. Evaluating countries’ medical cannabis regulations allows us to offer implications for lessons to be learned for the development of a successful medical cannabis regime in the UK.